(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Accounting is the process of recording financial transactions about a business. Given that the respondents here are taking Accountancy, Business, and Management Strand, they should be able to understand it because this is the guide, and it gives information on how they will transact every transaction. Most people talk about how hard accounting is. Of course, there is no easy major anywhere. However, some factors affect the way how the students understand it. First, they have poor analytical skills. Teacher’s strategy in teaching also affects the way of thinking of the students. Traditional teaching provides discussing and giving tests, while modern teaching provides activities that help them relate the topic to their experiences in life. This research contained the effectiveness of using high-order skills instead of using traditional teaching. A descriptive method was used in this study. This study aimed to improve the accounting skills of the students and identify the effectiveness of improving the accounting skills of Grade 12 Accountancy, Business, and Management (ABM)students in Bestlink College of the Philippines. This study comprised all students that presented facts regarding the nature and status of anything. It is concerned with the circumstances of the relationship that happened. The respondents were 50 selected Grade 12 ABM students in Bestlink College of the Philippines, S.Y. 2019–2020. The focus of this study was to improve their accounting skills through peer-to-peer tutorials. The researchers found out the teacher’s ways of teaching and their difficulties in analyzing critical situations can affect the understanding of the students. The conflicts in understanding terminologies may lead to malfunctions of transactions. The researchers found out that advance reading books about accounting, attending seminars that talk about accounting, and watching tutorials on social media can help the students improve their accounting skills. The purpose of accounting was to provide information to different users. The users utilized the information in making economic decisions. It can be depicted from some definitions made by accounting bodies. The researchers recommended advance reading books about accounting and watching tutorials for you to improve your accounting skills. Enhancing your logical and critical thinking by solving critical problems can help one solves a complicated problem in accounting.